Mercy Watson Goes For A Ride - DiCamillo, Kate; Van Dusen, Chris (Somerville, Mass. : Candlewick Press, 2009)
Mr. Watson's usual Saturday drive in his Cadillac with his favorite pig, Mercy, turns into an adventure when an unexpected passenger shows up in the back seat and Mercy finds herself behind the wheel.
new kids book 2023 fall.
Notable/Best Books (A.L.A.), January 2007
School Library Journal, June 2006
Booklist, May 2006
Kirkus Review, May 2006
2.7.
Keywords: Pigs -- Fiction; Watson, Mercy (Fictitious character) -- Fiction; Automobile driving -- Fiction; Humorous fiction